Persepsi Caring Behaviour Perawat Pada Pasien Pre Operatif - Ahya, Fadiatul; Nugroho, Erlangga Galih Zulva; Marianthi, Dewi; Hayati, Wirda; Rimadeni, Yeni; Sulistiani, Ria Purnawian; Amalia, Diya (Journal Keperawatan, 2024)
Background: Caring behavior is a form of basic nursing practice that is shown by being patient, honest, confident, present, touched, affectionate and humble in carrying out the actions to be performed so that patients feel comfortable and assisted in a faster healing process for patients. Purpose: This study aims to describe the perceptions of caring behavior of nurses in preoperative patients at Meuraxa Hospital in Banda Aceh Methods: The type of research in this research is quantitative by using the correlation method with the Cross Sectional Study approach with a total sample of 57 respondents. Results: The level of caring given by nurses to preoperative patients was mostly in the good category, namely as many as 40 respondents (70.2%) and found that there was a significant relationship to the perception of caring behavior of nurses in preoperative patients at Meuraxa Hospital, Banda Aceh with a score p.value 0.032 < 0.005 Conclusion: There is a significant relationship in the description of nurses' perceptions of caring behavior in preoperative patients at Meuraxa Hospital, Banda Aceh